Comprehensive quantitative evaluation and mechanism analysis of influencing factors on yield and quality of cultivated Gastrodia elata Blume - Jiang, Xiaojun; Dai, Jing; Huang, Yi; Zhao, Dan; Yin, Yao; Lin, Qiao; Hou, Mengmeng; Jin, Hong (Scientific reports, 2025)
Gastrodia elata Blume ( G. elata Bl.) is a dual-purpose herb for medicine and food. Wild resources are depleted, and there is a significant decrease in yield or quality when they are cultivated artificially. However, what factors led to the decline is still unclear. In this study, based on comprehensive data under multiple production regions, hierarchical partitioning and partial least squares path modeling were used for the first time to quantitatively evaluate the dominant influencing factors and mechanism for the yield and quality of cultivated G. elata Bl.. The results showed that all G. elata Bl. were categorized into two cultivated subspecies G. elata Bl. f. elata and G. elata Bl. f. glauca . The Proteobacteria was the most dominant phylum for bacteria with 33.59%, and Ascomycota for fungi with 46.33% based on the amplicon sequencing. Armillaria relative abundance, soil available potassium, and temperature seasonality were the key factors. Their independent effects were 74.14%, 24.78%, and 20.36% on yield, and 36.83%, 25.63%, and 21.30% on quality, respectively. Plant subspecies directly determined the yield and quality ( P < 0.01). Soil physical properties affected chemical properties, which in turn affected biological properties and ultimately yields ( P < 0.05). Meanwhile, soil physical properties affected quality by influencing soil chemical properties ( P < 0.01). In conclusion, our study contributed novel insight to optimize cultivation strategies of G. elata Bl..